Toolkits for Policymakers to Green the Financial System - World Bank (World Bank, Washington, DC, 2021)
The World Bank works with government policy makers, regulators, central banks, and supervisors in implementing reforms to build a sustainable financial system. Such reforms must align the financial system with the goals of the Paris Agreement on climate change and the Sustainable Development Goals (SDGs). This report aims to provide a comprehensive overview of the range of approaches that public authorities could take to promote green finance and manage climate-related and environmental risks. The toolkits presented in this report aim to help countries set clear and predictable strategies, increase the attractiveness of green investments, and better understand and manage climate-related and environmental risks. Targeted financial public authorities may include Ministries of Finance or related government agencies, as well as central banks and financial supervisors/regulators. The report is not designed to provide an in-depth analysis of each toolkit. Rather, it summarizes the key characteristics of each approach, provides key actions to drive implementation, and references other publications that provide more detailed guidance.